MAIN ASPECTS OF USING MOBILE MARKETING FOR MARKETING RESEARCH - HANZHALA, Iryna; BURTSEVA, Tetiana; PEPCHUK, Sergey (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article examines the use of mobile marketing for marketing research, mobile marketing is an effective approach that allows you to collect large amounts of data, analyze user behavior and improve marketing strategies based on the results obtained. Mobile devices such as smartphones and tablets are the primary tools for interacting with consumers, so mobile marketing provides an opportunity to obtain relevant data about the consumer audience. There is an increasing use of QR codes, the importance of which is growing recently. Thus, digital marketing is becoming part of integrated marketing communications and is now essential to the success of any company in any industry. The article considers the main features of methods, tools and technologies of mobile marketing as a modern approach to business communication. A system is considered that subordinates all mobile marketing tools, including mobile applications, at the stages of their development, implementation and use, from optimization in the market to the use of QR codes. The use of QR codes has grown significantly in recent years, as they have become a convenient tool for information transfer and interactive interaction in many areas.The article also examines the growth in the number of subscriptions to mobile networks worldwide from 2016 to 2024, with forecasts up to 2028. The growing number of mobile subscriptions shows that developers, businesses and users are interested in apps, which proves the relevance of this topic. Mobile marketing is a global trend that has a significant impact on the economy, society and technology development. The publication outlines the advantages and disadvantages, as well as the potential for further development of mobile marketing.
Keywords: mobile marketing; digital marketing; SMS and MMS marketing; mobile applications and advertising; artificial intellect; QR codes; AR and VR technologies